1982
DOI: 10.1128/aac.21.2.341
|View full text |Cite
|
Sign up to set email alerts
|

In vitro activity of N-formimidoyl thienamycin and other beta-lactam antibiotics against methicillin-resistant Staphylococcus aureus

Abstract: Of 43 isolates of methicillin-resistant Staphylococcus aureus, 90% were inhibited by 8 ,ug or less of N-formimidoyl thienamycin per ml by the agar-dilution technique. Cefamandole, cefotaxime, cefoperazone, moxalactam, and cefsulodin showed relatively poor activity. Vancomycin was the most active compound by weight, inhibiting 93% of strains at 1 ,ug/ml. Third-generation cephalosporins, including cefoperazone, cefotaxime, and cefsulodin, are generally less active than cephalothin against staphylococci and other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

1983
1983
1986
1986

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 14 publications
1
14
0
Order By: Relevance
“…Imipenem is a ,B-lactam antibiotic with a unique structure and a broad activity (8,12); there have been reports of in vitro activity against methicillin-resistant (MR) Staphylococcus aureus (16). However, studies in our and other institu-tions have shown differences in the in vitro susceptibility of methicillin-susceptible versus MR S. aureus strains to imipenem (17).…”
mentioning
confidence: 86%
“…Imipenem is a ,B-lactam antibiotic with a unique structure and a broad activity (8,12); there have been reports of in vitro activity against methicillin-resistant (MR) Staphylococcus aureus (16). However, studies in our and other institu-tions have shown differences in the in vitro susceptibility of methicillin-susceptible versus MR S. aureus strains to imipenem (17).…”
mentioning
confidence: 86%
“…aureus and Staph. 79 0305-7453/83/12D079 + 09 S02.00/0 © 1983 The British Society for Antimicrobial Chemotherapy epidermidis, including some methicillin-resistant strains (Cherubin et al, 1981;Livingston et al, 1981;Thompson et al, 1982) justified in-vivo studies of this drug in infections caused by these organisms. We selected a model of left-sided Staph.…”
Section: Bacteroides Fragilis Carbenicillin-resistant Pseudomonas Aementioning
confidence: 99%
“…Its spectrum of action is unusually broad, with important in-vitro activity against the majority of bacteria often creating therapeutic problems, such as (Cherubin et al 1981;Kesado, Hashizume & Ashai, 1980;Kesado et al, 1982;Livingston, Elliott & Cobbs, 1981;Michael, Alford & McGee, 1981;Thompson, Fischer & Wenzel, 1982;Verbist & Verhaegen, 1981). Only a small incidence of crossresistance to penicillins and cephalosporins has been demonstrated with imipenem.…”
Section: Introductionmentioning
confidence: 99%
“…19 However, concerns about the expense and possible toxicity of vancomycin as well as the specter of emergence of resistance to this agent have led to the evaluation of a plethora of newer antimicrobics for their activity against MRSA. 20,21 Although recent data demonstrate an ever-increasing prevalence of MRSA isolations, 12 reported rates may in fact underestimate the true extent of the problem. It has been suggested that small community hospitals which lack ongoing infection control programs may frequently underreport the actual numbers of MRSA isolations/ infections.…”
mentioning
confidence: 99%